Exploring Efl Students’ Practice and Challenges by Using Quizizz in Learning Reading Comprehension - Kristiana, Meri; Srisudarso, Mansyur; Abas, Totoh Tauhidin (Peneliti.net, 2024)
Learning to read English is often faced with various challenges, especially in the context of students learning English as a foreign language. One of the problems that arise is the feeling of boredom that some students feel during the process of learning to read. This boredom can affect students' motivation and focus in understanding reading material, which in turn can have a negative impact on student's level of understanding of the reading material. The research objective is to explore using the Quizizz platform as an ICT tool in learning to read. Method in this study is using qualitative approach with phenomenology design. The participant are 5 students from junior high school. Data analysis follows the approach of Miles and Huberman. The result found that the findings focus on aspects of student behavior during learning reading through Quizizz. The findings indicate that using technology for learning is equally important in building a more interactive classroom. Quizizz in learning to read English can build active interaction and participation of students during the learning process. Therefore, students involved in the learning process can develop their ability to understand English texts better.